2017
DOI: 10.1103/physrevd.96.033005
|View full text |Cite
|
Sign up to set email alerts
|

Improved determination of the U235 and Pu239<

Abstract: We present the results of a combined fit of the reactor antineutrino rates and the Daya Bay measurement of σ f,235 and σ f,239 . The combined fit leads to a better determination of the two cross sections per fission: σ f,235 = 6.29 ± 0.08 and σ f,239 = 4.24 ± 0.21 in units of 10 −43 cm 2 /fission, with respective uncertainties of about 1.2% and 4.9%. Since the respective deviations from the theoretical cross sections per fission are 2.5σ and 0.7σ, we conclude that, if the reactor antineutrino anomaly is not du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
(26 reference statements)
2
11
0
Order By: Relevance
“…[15][16][17] that the allowed parameter space is compatible with earlier anomalies from LSND [18,19], MiniBooNE [20], GALLEX [21], and SAGE [22]. On the other hand, a number of authors [23][24][25][26] have argued that the RAA may be due to the theoretical uncertainties in the flux calculations. Recent antineutrino flux evolution results from Daya Bay are in tension with the sterile-neutrino-only explanation of RAA [27].…”
Section: Introductionsupporting
confidence: 60%
“…[15][16][17] that the allowed parameter space is compatible with earlier anomalies from LSND [18,19], MiniBooNE [20], GALLEX [21], and SAGE [22]. On the other hand, a number of authors [23][24][25][26] have argued that the RAA may be due to the theoretical uncertainties in the flux calculations. Recent antineutrino flux evolution results from Daya Bay are in tension with the sterile-neutrino-only explanation of RAA [27].…”
Section: Introductionsupporting
confidence: 60%
“…In this study, we refer to these isotopic IBD yields as σ 5 , σ 8 , σ 9 , and σ 1 for the isotopes Pu, respectively. To obtain isotopic IBD yields in this analysis, we use a least-squares test statistic similar to those utilized in previous studies [38,40,41]:…”
Section: Global Fits To Existing Reactor Ibd Yield Measurementsmentioning
confidence: 99%
“…Measurement of variation in inverse beta decay (IBD) detection rates arising from evolution of reactor fuel content at the Daya Bay experiment has provided evidence that incorrect modeling ofν e production by individual fission isotopes may be at least partially responsible for the flux anomaly [38]. New global fits comparing measured IBD spectra [39] and integrated yields [40,41] between reactor experiments have suggested that modeling of…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is a partial mistake in the currently adopted reactor neutrino flux models, confirmed also by the presence of the "bump" (discussed above) in the region of the spectrum between 4 and 6 MeV and by the partial inconsistency with the fuel evolution results observed by Daya Bay and RENO. As underlined in [66][67][68], such a solution for the reactor antineutrino anomaly would require mainly a theoretical revaluation of the 235 U reactor antineutrino flux.…”
Section: Open Issues In Sbl Reactor Experimentsmentioning
confidence: 99%